Economic policy and state intervention : selected papers of T.N. Srinivasan - Srinivasan, T. N.; Narayana, N. S. S. (New Delhi : Oxford University Press, 2001)
With reference to developing countries.
Includes bibliographical references.
Keywords: India -- Economic policy -- 1991-